Behaviour of steel reinforced concrete columns with high strength materials - Cai, Yan Qing (2017)
High strength construction materials are now attractive for composite steel-concrete construction due to their economic and architectural advantages. However, the current design codes for Steel Reinforced Concrete (SRC) columns are in general only applicable to normal strength materials. It is only allowed in Eurocode 4 (EC4) for concrete class C20/25-C50/60 and steel grades S235-S460 to be used in composite columns. On the other hand, it is permissible in Eurocode 2 (EC2) for higher strength concrete (up to C90/105) while Eurocode 3 (EC3) steel grade up to S690. While there are a lot of published works which focused on SRC columns with normal strength materials (fck ≤ 50 N/mm2 and fy ≤ 460 N/mm2), research on SRC columns with high strength materials is rather limited. This leads to insufficient test data to establish the validity of using high strength materials in SRC columns in EC4. Therefore, this study is geared to further extend the scope of EC4 to include the usage of high strength materials in SRC columns through numerical and theoretical study. A comparative study of the current confined concrete models was carried out to identify the most accurate model to be used in design and simulation. An analytical method was then proposed to predict the behaviour of SRC columns, taking into account the effect of strain-compatibility and lateral confinement. Next, a finite element (FE) model was developed to analyse the behavior of SRC columns under concentric and eccentric axial loading by ABAQUS. The FE model was validated with published test data from other researchers. Based on the reliability of the finite element simulation, a series of parametric study were conducted by varying certain variables, i.e. the structural steel strength (up to 690 N/mm2), concrete strength (up to 90 N/mm2), volumetric ratio, diameter and spacing of lateral reinforcement, column length and eccentricity ratio. The results were compared with EC4 and the proposed method. It is shown that the ultimate strengths of SRC columns increased linearly with the increase of material strength for short columns. However, increasing material strength had negligible effect on column strength for slender columns. Ultimate strength of SRC columns increased by either increasing the diameter and volumetric ratio of hoops or decreasing the spacing of hoops. The diameter, spacing and volumetric ratio of hoops had significant effects on the ultimate strength of column reinforced with high strength steel. The effect of material strength on the column strength was significant for column with smaller eccentricity. For column with higher eccentricity, the effect of material strength was only significant for concrete strength less than 70 Mpa. The comparison indicated that EC4 was conservative in predicting the bearing capacity of SRC columns with material strength (fc ≤ 90 N/mm2 and fy ≤ 550 N/mm2). However, EC4 overestimated the ultimate strength of SRC columns with steel strength higher than 550 N/mm2. Nevertheless, the proposed method was conservative in predicting the bearing capacity of columns with normal and high strength materials. The scope of EC4 can be further extended to cover a wider range of material strength including concrete strength up to 90 N/mm2 and yield strength of steel up to 550 N/mm2. The proposed method, which considering strain-compatibility and lateral confinement effects, can accurately predict the strength of SRC columns with concrete strength up to 90 N/mm2 and steel strength up to 690 N/mm2.